Two-phase flow boiling in small channels: a brief review - Sardeshpande, Madhavi V.; Ranade, Vivek V. (Sadhana-Academy Proceedings in Engineering Sciences, 2013)
Boiling flows are encountered in a wide range of industrial applications such as boilers, core and steam generators in nuclear reactors, petroleum transportation, electronic cooling and various types of chemical reactors. Many of these applications involve boiling flows in conventional channels (channel size >= 3 mm). The key design issues in two phase flow boiling are variation in flow regimes, occurrence of dry out condition, flow instabilities, and understanding of heat transfer coefficient and vapor quality. This paper briefly reviews published experimental and modeling work in these areas. An attempt is made to provide a perspective and to present available information on boiling in small channels in terms of channel size, flow regimes, heat transfer correlations, pressure drop, critical heat flux and film thickness. An attempt is also made to identify strengths and weaknesses of published approaches and computational models of boiling in small channels. The presented discussion and results will provide an update on the state-of-the-art and will be useful to identify and plan further research in this important area.
Keywords: Boiling; dry-out; heat transfer; instabilities; small channel; two-phase flow

Two phase flow boiling pressure drop in small channels - Sardeshpande, Madhavi V.; Shastri, Parikshit; Ranade, Vivek V. (IUTAM Symposium on multiphase flows with phase change: challenges and opportunities, 2015)
Two-phase pressure drop, flow instability and boiling regime identifications are an essential step in the design of a variety of plant in the power and process industries. Despite the wide spread applications, significant experimental data on flow boiling in small channel is not available. In the present work, experimental set-up was designed for studying boiling flows in 19 mm ID tube and identifies flow regimes at various mass and heat flux conditions by varying inlet fluid temperature. The steady-state pressure data was collected and flow regimes identified using pressure drop and pressure fluctuations inside the channel. (C) 2015 The Authors. Published by Elsevier B.V.
Keywords: flow boiling; flow instability; pressure drop; regime identification

Two-phase flow boiling in 19mm tube: experiments and CFD modelling - Sardeshpande, Madhavi V.; Raymond, Barlev; Ranade, Vivek V. (Canadian Journal of Chemical Engineering, 2016)
Boiling flows are encountered in a wide range of industrial applications such as boilers, nuclear reactors, electronic cooling, and various types of chemical reactors. Heat transfer coefficients, flow boiling regimes, flow instabilities, pressure drops, and conditions like dry-out are some of the key issues in every boiling flow study. It is observed that a limited experimental database is available for the 19mm ID channel diameter, i.e. a typical tube diameter of steam generator. Therefore, in the present work, the experimental setup was designed for studying boiling flows in a 19mm ID tube in such a way that different flow regimes occurring in a steam generator tube (from pre-heating of sub-cooled water to dry-out) could be investigated by varying inlet conditions. The reported results cover a reasonable range: 8-27kW/m(2) and 2.9-5.9kg/m(2)s heat and mass flux conditions, respectively. A basic computational flow model was also developed to facilitate interpretation of the obtained data. The presented design of the experimental setup and the approach of mimicking different types of steam generator tubes as well as presented experimental and simulated results are useful for gaining insight into complex boiling flows in tubes, and provide a sound basis for further work in this area.
Keywords: CFD; Flow regimes; two-phase flow boiling; vapour quality

Two-phase flow boiling pressure drop in small channels - Sardeshpande, Madhavi V.; Shastri, Parikshit; Ranade, Vivek V. (International Journal of Heat and Fluid Flow, 2016)
Two-phase flow boiling in small channels finds a variety of applications in power and process industries. Heat transfer, boiling flow regimes, flow instabilities, pressure drop and dry out are some of the key issues related to two-phase flow boiling in channels. In this work, the focus is on pressure drop in two-phase flow boiling in tubes of 19 mm diameter. These tubes are typically used in steam generators. Relatively limited experimental database is available on 19 mm ID tube. Therefore, in the present work, the experimental set-up is designed for studying flow boiling in 19 mm ID tube in such a way that any of the different flow regimes occurring in a steam generator tube (from pre-heating of sub-cooled water to dry-out) can be investigated by varying inlet conditions. The reported results cover a reasonable range of heat and mass flux conditions such as 9-27 kW/m(2) and 2.9-5.9 kg/m(2) s respectively. In this paper, various existing correlations are assessed against experimental data for the pressure drop in a single, vertical channel during flow boiling of water at near-atmospheric pressure. A special feature of these experiments is that time-dependent pressures are measured at four locations along the channel. The steady-state pressure drop is estimated and the identification of boiling flow regimes is done with transient characteristics using time series analysis. Experimental data and corresponding results are compared with the reported correlations. The results will be useful for understanding key aspects of flow boiling in small channels. (C) 2016 Elsevier Inc. All rights reserved.